Peranan Perguruan Tinggi dalam Pengembangan Kompetensi Profesional Calon Tenaga Pendidik - Suhaimi, Suhaimi (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2016)
The efforts to create the professional educators, in fact, are never easy. There are some problems found not only in the preparation area of an educator but also in its implementation. When a teacher candidate takes an education study program in a higher education, then his/her knowledge and skills are trained to be professional. The higher education becomes the role of creating a profesional teacher as well as facilitating the understanding of concept and theory of how to be a professional qualified teacher. An intellectual teacher candidate should have a high self-awareness in developing his/her knowledge and attitude as the process of education. The process of education at a higher education should provide an ample opportunity for its student to be optimally developed.